Simulation of the Clash between Cultural Values in Heterogeneous Society using Numerical Methods - Sahani, Suresh Kumar; Karna, Santosh Kumar (Journal of Posthumanism, 2024)
Cultural value conflicts, which have their origins in different moral codes, traditions, and social standards, are a reliable source of social friction in communities that are comprised of people from different backgrounds. When it comes to effectively forecasting or controlling the dynamics of such disputes, traditional qualitative techniques often provide inadequate results. In this study, a mathematical framework is presented for the purpose of simulating cultural value conflicts via the use of numerical approaches that are based on differential equation modelling and agent-based systems. We construct a conflict index function that simulates interactions between cultural groups across time. This function is based on Hofstede's cultural dimensions theory as well as Inglehart–Welzel's cultural map. The quantification of cultural resilience and conflict escalation in hypothetical multicultural configurations is accomplished by the enhanced use of finite difference techniques and interaction models inspired by the Lotka–Volterra model. In order to undertake empirical validation, census-based demographic data and World Values Survey (WVS) datasets from Canada and the Netherlands, two of the most notable multicultural countries in the world, are used. The findings indicate that there are non-linear patterns of cultural convergence and divergence that occur under different integration approaches and population changes for different populations. The data that we have obtained provide a quantitative foundation for policy choices that are intended to improve social cohesiveness and reduce the amount of cultural polarization that exists. This research marks a big step forward in the process of incorporating numerical simulation into the investigation of sociocultural conflicts.